Penyuluhan Personal Hygiene Saat Menstruasi dengan Kejadian Keputihan pada Remaja Putri Kelas X di SMA Negeri 3 Ambon - Arindiah Puspo Windari; Siti Rochmaedah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Feminine hygiene (personal hygiene), especially during menstruation is often ignored by adolescents, if they do not maintain genital hygiene properly, then in a humid state, fungi and bacteria that are in the female area will thrive. The use of underwear that uses thin materials and not absorbing sweat can also make the female area moist and smelly, making it easier for fungi and bacteria to grow. smells can make it easier for fungi and bacteria to nest and the length of time using sanitary napkins that are more than 2-3 hours can make it easier for fungi and bacteria to nest.The aim is to provide new insights to adolescent girls about how to maintain personal hygiene during menstruation. about how to maintain personal hygiene during menstruation and the incidence of vaginal discharge in high school students in class X.I at SMA Negeri 3 Ambon. The method of this community service was carried out using the lecture method and question and answer discussions as well as pre and post tests. The result is an increase in knowledge of adolescent girls regarding menstrual hygiene and the incidence of whitish discharge.